Position And Material Contents Of Ministerial Regulation In the Perspective of the Presidential System - Hari Sanjaya; Jasni bin Sulong (ISNU Sumatera Utara, 2024)
Regulatory obesity at the central and regional levels causes problems in the structuring of legislation. Very diverse Ministerial Regulations make it difficult for local governments to follow up. The problems studied in this study are, first, what is the position and content of ministerial regulations in the perspective of legislation and the presidential system in Indonesia? Second, how are efforts to avoid obesity in the formation of ministerial regulations in the administration of government? The two problems will be analyzed in a qualitative descriptive manner, using legislative and conceptual approaches. The results of this study conclude, first, ministerial regulations are basically not included in the hierarchy of laws and regulations, it is just that they can be issued by the minister as long as there is authority or order from a higher law to regulate them and only applies inwards for the benefit of the institution he leads. However, ministers/ministries in the presidential system are not responsible to the parliament but to the President, so the one who should set the laws and regulations should be the President; Second, to avoid obesity in the formation of ministerial regulations, the president only needs to form a Government Regulation or Presidential Regulation, and there is no need to delegate it to the minister to form the implementing regulations.